Empagliflozin in patients with heart failure, reduced ejection fraction, and volume overload: EMPEROR-reduced trial - Packer, Milton; Anker, Stefan D.; Butler, Javed; Filippatos, Gerasimos; Ferreira, Joao Pedro; Pocock, Stuart J.; Sattar, Naveed; Brückmann, Martina; Jamal, Waheed; Cotton, Daniel; Iwata, Tomoko; Zannad, Faiez (Journal of the American College of Cardiology, 2021)
Background - Investigators have hypothesized that sodium-glucose cotransporter 2 (SGLT2) inhibitors exert diuretic effects that contribute to their ability to reduce serious heart failure events, and this action is particularly important in patients with fluid retention. - Objectives - This study sought to evaluate the effects of the SGLT2 inhibitor empagliflozin on symptoms, health status, and major heart failure outcomes in patients with and without recent volume overload. - Methods - This double-blind randomized trial compared the effects of empagliflozin and placebo in 3,730 patients with heart failure and a reduced ejection fraction, with or without diabetes. Approximately 40% of the patients had volume overload in the 4 weeks before study enrollment. - Results - Patients with recent volume overload were more likely to have been hospitalized for heart failure and to have received an intravenous diuretic agent in an outpatient setting in the previous 12 months, and to experience a heart failure event following randomization, even though they were more likely to be treated with high doses of a loop diuretic agent as an outpatient (all p < 0.001). When compared with placebo, empagliflozin reduced the composite risk of cardiovascular death or hospitalization for heart failure, decreased total hospitalizations for heart failure, and improved health status and functional class. Yet despite the predisposition of patients with recent volume overload to fluid retention, the magnitude of these benefits (even after 1 month of treatment) was not more marked in patients with recent volume overload (interaction p values > 0.05). Changes in body weight, hematocrit, and natriuretic peptides (each potentially indicative of a diuretic action of SGLT2 inhibitors) did not track each other closely in their time course or in individual patients. - Conclusions - Taken together, study findings do not support a dominant role of diuresis in mediating the physiological changes or clinical benefits of SGLT2 inhibitors on the course of heart failure in patients with a reduced ejection fraction. (EMPagliflozin outcomE tRial in Patients With chrOnic heaRt Failure With Reduced Ejection Fraction [EMPEROR-Reduced]; NCT03057977)
Gesehen am 27.07.2021